2020
DOI: 10.3389/fphys.2019.01590
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor Muscles in COPD: The Rationale for Rehabilitative Exercise Training

Abstract: Exercise training as part of pulmonary rehabilitation is arguably the most effective intervention to improve tolerance to physical exertion in patients with chronic obstructive pulmonary disease (COPD). Owing to the fact that exercise training has modest effects on exertional ventilation, operating lung volumes and respiratory muscle performance, improving locomotor muscle structure and function are key targets for pulmonary rehabilitation in COPD. In the current concise review, we initially discuss whether pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 157 publications
(240 reference statements)
0
32
0
1
Order By: Relevance
“…7 General principles of exercise training are no different in COPD patients from healthy controls or even athletes, although the physiological response might be altered in COPD patients. 5,122 Aerobic exercise or endurance training in COPD patients specifically improves exercise tolerance, breathlessness, exercise induced hyperinflation and stimulates a muscle fiber shift back to more oxidative type I fibers, improving mitochondrial capacity and thus efficiency. [123][124][125] Interval training is a variation to continuous endurance training, with short periods of highintensity exercise alternated with periods of lower intensity or rest.…”
Section: Interventions Primarily Targeting Sarcopenia In Copd Exercismentioning
confidence: 99%
See 2 more Smart Citations
“…7 General principles of exercise training are no different in COPD patients from healthy controls or even athletes, although the physiological response might be altered in COPD patients. 5,122 Aerobic exercise or endurance training in COPD patients specifically improves exercise tolerance, breathlessness, exercise induced hyperinflation and stimulates a muscle fiber shift back to more oxidative type I fibers, improving mitochondrial capacity and thus efficiency. [123][124][125] Interval training is a variation to continuous endurance training, with short periods of highintensity exercise alternated with periods of lower intensity or rest.…”
Section: Interventions Primarily Targeting Sarcopenia In Copd Exercismentioning
confidence: 99%
“…123,127 Resistance training consistently increased muscle mass, and was more effective in counteracting muscle atrophy than endurance training in COPD. 122 Therefore, a combination of both endurance or interval training and resistance training, as commonly applied in PR, might be optimal to improve muscle mass, strength and endurance in sarcopenic COPD patients. Theoretically, oxygen supplementation during exercise would enable a higher training intensity and thus would yield better improvements in muscle mass and strength.…”
Section: Interventions Primarily Targeting Sarcopenia In Copd Exercismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that, in people with pulmonary diseases, low muscle strength is associated with physical inactivity ( Osthoff et al, 2013 ) and is an independent predictor of morbidity and mortality independent of the degree of respiratory limitation ( Swallow et al, 2007 ). Consequently, the key target in rehabilitation for pulmonary diseases should be improving locomotor muscle structure and function, as exercise results in reduced benefits on exertional ventilation, operating lung volumes, and respiratory muscle performance ( Marillier et al, 2020 ). Moreover, the performance of physical exercise is advised as adjuvant non-pharmacological treatment during pulmonary fibrosis rehabilitation ( Spruit et al, 2009 ).…”
Section: Respiratory Systemmentioning
confidence: 99%
“…Los resultados de nuestro estudio han mostrado un deterioro funcional y de calidad de vida significativamente mayor en los pacientes EPOC con SL. Por ello, en esta población las actividades relacionadas con la salud publica deben ir enfocadas a la instauración de intervenciones educativas que promuevan cambios de comportamiento y estilo de vida a largo plazo, como rehabilitación física y pulmonar 42 .…”
Section: Discussionunclassified